COMPLIMENT RESPONSES USED BY INDONESIANS LEARNING ENGLISH BASED ON THE COMPLIMENT TOPICS AND SOCIAL STATUSES - Yustika Sari (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
This article is a study of compliment responses used by Indonesians learning English to respond to English compliments based on the compliment topics (appearance and ability) and social statuses of the addressor (higher, equal, and lower). The data were collected using a Discourse Completion Test (DCT) and a questionnaire. The results of this study showed that appreciation token was the most frequently used in all situations given. The results also revealed that the subjects' background (academic year cohort) did not give a significant effect on the preference of the types of compliment responses.